Inovasi Peran Hablum Minal Alam dalam Meningkatkan Pendidikan Religius di Perkumpulan Tani Pemuda Darul Mukmin Sukorejo Pasuruan - miftah, mifthul arifin; Saifulah; Ahmad Marzuki; Anang Sholikhudin (Jurnal Penelitian Ilmiah INTAJ, 2024)
The National Disaster Management Agency (BNPB) said that in the last 10 years, disasters in the country have continued to increase. Which is caused by the decline and erosion of human morals and consciousness in protecting and utilizing nature. Therefore, in this study, the researcher wants to analyze and describe the role of the Darul Mukmin Youth Farmers Association in improving religious education through habl min al-'ālam innovation, and the implementation of habl min al-'ālam innovation in improving religious education in the Darul Mukmin Sukorejo Pasuruan Youth Farmers Association. It is field research and uses a qualitative approach in descriptive form. The results of this study show that: the background of the role of the Darul Mukmin Youth Farmers Association in improving religious education through habl min al-'ālam innovation includes, (a) religious education is implemented through Islamic values combined with agriculture and habl min al-'ālam, (b) religious education is combined with agriculture in the form of collaborative activities between agricultural and religious activities (c) religious education covers the field of habl min al-Allāh, habl min al-nās and habl min al-'ālam. Meanwhile, the implementation of hablum minal 'alam innovation in improving religious education in the Darul Mukmin Sukorejo Pasuruan Youth Farmers Association includes: (a) aqidah such as piety, (b) morals such as honesty and sincerity and (c) community such as responsibility.